ARE SATISFIED STUDENT CAN DEVELOP THEIR EMPLOYABILITY BETTER ? - rezki ashriyana sulistiobudi; Puspita Adhi Kusuma Wijayanti (Journal of Educational, Health and Community Psychology, 2019)
Unemployment rate of vocational high school graduates is a big problem in developing country like Indonesia, so they have to develop their ability to employ earlier. Schools become one of important factors to optimize employability development of the students. The more they are satisfied with the school, the more they have higher needs to grow, develop themselves to achieve their goal of work. This study aims to determine the contribution of school satisfaction and the dimensions to employability development of the students. The study was conducted to 368 vocational high school students in West Java, Indonesia. The result indicates that school satisfaction was positively contribute to employability development. Achievement, school management, teacher-student relationship, and academic learning were play significant role to employability development. Â Create the school to be more positive environment for student can make them develop optimally. Therefore, they can prepare their readiness better to work after graduate from vocational high school.Â  Â